Audit of appropriate use of platelet transfusions: validation of adjudication criteria. Issue 1 (19th October 2017) - Etchells, M.; Spradbrow, J.; Cohen, R.; Lin, Y.; Armali, C.; Lieberman, L.; Cserti‐Gazdewich, C.; Pendergrast, J.; Callum, J.
Abstract : Background and Objectives: Platelet (PLT) transfusions must be used appropriately, as they are in chronic short supply, costly and risky to patients. The goals of this audit were to: (1) validate preset adjudication criteria through an audit of appropriateness at four large academic hospitals; (2) identify variability in appropriateness across medical services, physician specialties or hospital locations; and (3) inform logistical or educational interventions that may reduce inappropriate use. Materials and Methods: A chart review of two hundred patients receiving PLT transfusions was performed. Fifty consecutive transfusion episodes per site were audited in detail. Each transfusion episode was independently adjudicated as appropriate or inappropriate by two transfusion specialists based on predetermined criteria. Results: The adjudication criteria performed well with simple agreement of 95% (kappa statistic 0·83) between reviewers. Overall, 78% (95% CI: 72–84%) of PLT transfusions were adjudicated as appropriate, with results varying significantly by hospital site (range 62–94%). Prophylactic transfusions for non‐bleeding patients had the highest proportion of appropriateness (85%, n = 80), and therapeutic transfusions for bleeding patients had the lowest (73%, n = 99). The lowest levels of appropriate platelet transfusions were observed in the operating rooms (60%) and when ordered by the general surgery service (55%). Conclusions: One in five platelet transfusions may be unnecessary, suggesting that interventions to improve PLT transfusion practice are warranted.